The Impact of Psychological Distress on the Occupational Well-Being of Sexual and Gender Minorities - Pereira, Henrique (2022)
Background: Discrimination against sexual and gender minorities in occupational settings has been an important topic of research. However, little is known about this impact in Portuguesespeaking people. Methods: 305 Portuguese and Brazilian participants who identified as lesbian, gay, bisexual, transgender, queer, intersex, asexual, and other sexual and gender identities (LGBTQIA+) completed an online survey comprising sociodemographic questions, a set of scales to assess psychological distress, and a set of scales to assess occupational well-being. Results: Participants had higher levels of burnout, depressive symptoms, and anxiety and lower levels of work-related quality of life, engagement, and self-efficacy at work compared to the defined cut-off points for normative populations, with asexual and bisexual people appearing to be the most affected. Significant correlations were found for all variables, and psychological distress was a significant predictor of lower occupational well-being. Conclusions: These findings are useful for understanding the occupational health of LGBTQIA+ people and suggest efforts to improve the climate in the workplace for this population.